Characterization of the rhizophora particleboard as a tissue-equivalent phantom material bonded with bio–based adhesive - Taghizadeh Tousi, Ehsan; Hashim, Rokiah; Bauk, Sabar; Suhaimi Jaafar, Mohamad; Mohammad Hamdan Abuarra, Ali; Mahmoud Al-Jarrah, Amer; Ababneh, Baker; Taghizadeh Tousi, Afsaneh; Saleh Ali Aldroobi, Khalid (Maderas. Ciencia y Tecnología, 2025)
In this study, some characteristics of Rhizophora spp. particleboards bonded with Serishoom (traditional animal–based adhesive) as a phantom material was investigated. The Rhizophora spp. particleboards were fabricated in two Serishoom adhesive treatment levels (6% and 12%) with three Rhizophora spp. particle sizes (≤ 149 µm, 149 µm – 500 µm, and 500 µm – 1000 µm) at 1 g.cm-3 of the target density. The internal bond strength and the dimensional stability of the Serishoom-bonded Rhizophora spp. particleboards were improved by using the smaller Rhizophora spp. particle size and the higher Serishoom adhesive treatment level. The effective atomic numbers of the Serishoom-bonded Rhizophora spp. particleboards were determineted to be 7,56 to 7,58 by an energy dispersive X-ray, which is in good agreement with those of water and breast tissue. In addition, the density distribution profiles of the fabricated Serishoom-bonded Rhizophora spp. particleboards were determined by the Kriging method with the use Surfer8 computer software, which indicated that there was good density homogeneity throughout the Serishoom-bonded Rhizophora spp. particleboards. The results showed a potential of the Serishoom-bonded Rhizophora spp. particleboard bonded with Serishoom to be used as a phantom material.